Моделювання впливу визначальних факторів на рівень державного боргу України - Роганова, Ганна Олександрівна; Климаш, Наталія Іванівна; Третяк, Катерина Володимирівна (My University, 2022)
У статті проведено дослідження динаміки цін на метали та сировину на світовому ринку та встановлено зростаючу тенденцію, що має вплив на економічне становище України. Авторами здійснено горизонтальний аналіз основних макроекономічних показників за 12 років. Встановлено, що у досліджуваний період рівень державного боргу зростав, а крім того, в умовах воєнних дій в Україні перевищить ВВП країни найближчим часом. У роботі розроблено економіко-математичну модель регулюючого впливу незалежних факторів на розмір зовнішнього державного боргу України. У якості факторів непрямої дії із числа основних макроекономічних показників та показників рівня цін на ф'ючерси сировини обрано тринадцять показників, які мають найбільший вплив. Адекватність моделі підтверджено за допомогою відповідних коефіцієнтів, що дає змогу стверджувати про тісний зв'язок між результуючим показником та факторами, що впливають на його формування. The role of public debt and its impact on the economic potential of the country is investigated in the scientific work. It was found that the higher the level of public debt, the greater the country's dependence on creditors. Given the economic troubles, the influx of financial and economic crises in recent decades, the Covid-19 pandemic and military actions on the territory of Ukraine, the government was forced to make loans in fairly significant amounts.The article examines the dynamics of prices for metals and raw materials on the world market and establishes a growing trend that has an impact on the economic situation of Ukraine. Given the fact that Ukrainian producers export metals and grains, price fluctuations affect the country's economic situation. The authors carried out a horizontal analysis of the main macroeconomic indicators for 12 years. It was established that during the period under study, the level of public debt increased, and in the conditions of a full-scale war in Ukraine, it will exceed the country's GDP. Although this phenomenon is common in the world economy, this situation is dangerous for Ukraine, since the country's credit ratings fell with the start of hostilities. The paper developed an economic-mathematical model of the regulatory influence of independent factors on the size of the state debt of Ukraine. Thirteen indicators, which have the greatest influence, were selected as factors of indirect action from among the main macroeconomic indicators and indicators of the price level of raw materials futures. The closeness of the relationship between the dependent variable Y and the independent variables X was assessed using statistical characteristics: the coefficient of determination, the correlation coefficient. With the help of these coefficients, the conformity of the built regression model with the actual data was checked. After establishing the closeness of the connection between the variables of the model, the significance of the connection was characterized using Fisher's F-test. Since the correlation coefficient is a sample characteristic that may deviate from its true value, the significance of the correlation coefficient was tested using the Student's t-test. The adequacy of the model was confirmed using the above-mentioned coefficients, which makes it possible to assert a close connection between the resulting indicator and the factors affecting its formation.
Keywords: державний борг; результуючий показник; економіко-математична модель; незалежні фактори впливу; public debt; resulting indicator; economic-mathematical model; independent influencing factors; кафедра фінансів